A German Language and Cultural Camp - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
A German Language and Cultural Camp was conducted between 2nd - 4th April 2016 at Nur Lembah Pangsun, Hulu Langat, Selangor.